The Development of AKK Learning Model (Active, Creative, Communicative) through Cartoon Media for Reading Comprehension of Mandarin Language Learning For the Tenth Graders - Roisyah, Kholis; Mintowati, Maria; Roni, Roni (International Journal for Educational and Vocational Studies, 2020)
This study aimed to examine the development of Mandarin learning models using AKK (Active, Creative, Communicative) based on cartoon media for reading comprehension learning, which contains (1) the process of developing the AKK learning model (Active, Creative, Communicative) through cartoon media, ( 2) the quality of the AKK learning model (Active, Creative, Communicative) through cartoon media, (3) the effectiveness of the AKK learning model (Active, Creative, Communicative) through cartoon media for reading comprehension learning to master Mandarin text for tenth graders. This developmental research uses the Research and Development (R&D) model proposed by Borg and Gall. Based on the use of this R&D model, the data collection of this study used questionnaire, interview, and documentation. The results of this study are the AKK learning model (Active, Creative, Communicative) through cartoon media for reading comprehension learning to master Mandarin language gets some results (1) the process of developing the AKK learning model (Active, Creative, Communicative) through cartoon media runs smoothly and appropriately, (2) the quality of the AKK learning model (Active, Creative, Communicative) through cartoon media for reading comprehension learning to master Mandarin language is very suitable as seen from the results of the RPP validator, material, instruments, and media validation, (3) the effectiveness of the AKK learning model (Active, Creative , Communicative) through cartoon media for reading comprehension learning to master Mandarin language, obtained results for products of 5.77 with a significance level of 5% and for the results of observations made continue to increase from 85%, 82.5%, 95%, and 97.5% based on Likerrt scale is very strong. The AKK Learning Model (Active, Creative, Communicative) through cartoon media for reading comprehension learning to master Mandarin language is very appropriate to be used in the learning process and there is an increase in the learning outcomes of students in class X IPS 1 of SMA Khadijah Surabaya.